BIAS ORIENTALISME DALAM JURNALISME TELEVISI: KRITIK ATAS REPRESENTASI PESANTREN DI MEDIA MAINSTREAM - Anjaha Naufal Muhammad; Wifdatun Nisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the manifestation of internal orientalism bias in Indonesian television journalism, with a focus on how pesantren (Islamic boarding schools) are systematically misrepresented by urban-centric mainstream media. Using Critical Discourse Analysis (CDA) and framing analysis as the primary methodological frameworks, this research critically investigates the controversy surrounding TRANS7's program